2016
DOI: 10.1212/cpj.0000000000000238
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing absolute lymphocyte count profiles in dimethyl fumarate–treated patients with MS

Abstract: Background:Delayed-release dimethyl fumarate (DMF), indicated for the treatment of patients with relapsing-remitting multiple sclerosis (MS), is a disease-modifying therapy with potential immunomodulatory and neuroprotective effects. In clinical trials, DMF was associated with reduced white blood cell and absolute lymphocyte counts. Current US prescribing information recommends obtaining a complete blood count, including absolute lymphocyte count (ALC), before initiating and during DMF treatment.Methods:We con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
114
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(128 citation statements)
references
References 19 publications
11
114
2
1
Order By: Relevance
“…Selective depletion of Th1 and Th17 cells would be expected to be protective in MS and could contribute to the therapeutic effect of DMF. Nevertheless, despite the loss of CXCR3 + and CCR6 + cells among lymphopenic patients taking DMF, these patients have not shown a superior clinical response to the drug to date (4, 31)…”
Section: Discussionmentioning
confidence: 99%
“…Selective depletion of Th1 and Th17 cells would be expected to be protective in MS and could contribute to the therapeutic effect of DMF. Nevertheless, despite the loss of CXCR3 + and CCR6 + cells among lymphopenic patients taking DMF, these patients have not shown a superior clinical response to the drug to date (4, 31)…”
Section: Discussionmentioning
confidence: 99%
“…7,8 In a recently published integrated analysis of phase 2b/3/long-term extension studies of DMF in MS (N = 2470), mean absolute lymphocyte counts (ALCs) decreased by approximately 30% during the first year of treatment, then plateaued, remaining higher than the lower limit of normal (0.91 × 10 9 /L) thereafter. 17 Of the 2099 patients treated for at least 6 months, 47 (2.2%) had ALCs less than 0.5 × 10 9 /L persisting for at least 6 months. 17 Mean ALCs remained greater than or equal to the lower limit of normal in 84% and 76% of patients during the first 6 and 12 months, respectively; of these patients, 0.1% and 0% later developed ALCs less than 0.5 × 10 9 /L persisting for at least 6 months.…”
Section: Gi Tolerability Profilementioning
confidence: 95%
“…17 Of the 2099 patients treated for at least 6 months, 47 (2.2%) had ALCs less than 0.5 × 10 9 /L persisting for at least 6 months. 17 Mean ALCs remained greater than or equal to the lower limit of normal in 84% and 76% of patients during the first 6 and 12 months, respectively; of these patients, 0.1% and 0% later developed ALCs less than 0.5 × 10 9 /L persisting for at least 6 months. 17 In the ENDORSE ongoing safety extension study, one case has been reported to date of progressive multifocal leukoencephalopathy (PML), an opportunistic infection, in a patient treated with DMF 240 mg three times daily in the setting of prolonged (≥6 months) severe lymphopenia (approximately <0.5 × 10 9 /L of 3.5 years' duration).…”
Section: Gi Tolerability Profilementioning
confidence: 95%
See 1 more Smart Citation
“…In fact, 61% of patients kept over the lower limit of the lymphocyte count (>910/mm 3 ). The incidence of lymphopenia (<500/mm 3 ) was 7% . Moderate‐to‐severe lymphopenia might increase the PML risk, and it is recommended to obtain the complete blood cell count and monitor the lymphocyte count for at least every 3 months during the DMF treatment.…”
Section: Four Questions and Answers For Dmf In The 2017 Supplement Ofmentioning
confidence: 99%